2013
DOI: 10.1002/anie.201307640
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a [2]Catenane from the Sodium Ion Templated Orthogonal Arrangement of Two Diethylene Glycol Chains

Abstract: An important feature for the efficient construction of a [2]catenane is the appropriate alignment of the individual precursor molecular components. [1] Although direct selfassembly of these components through intermolecular hydrogen bonding [2] and/or p-stacking interactions [3] is possible in some unique recognition systems, the use of an ionic template to bridge and preorganize them remains a commonly applied strategy. In addition to anions, [4] transition-metal cations [5] are the most frequently used ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 46 publications
(37 reference statements)
2
26
0
1
Order By: Relevance
“…Nevertheless, an example of an alkaline cation template synthesis of a [2]catenane formed under thermodynamic control has been reported by Chiu and co-workers (Scheme 20 ). [ 86 ] The system combines diamine 69 with dialdehyde 70 through reversible imine bond formation in the presence of a sodium salt in a low polarity solvent to give the [2]catenane 72-Na I (Scheme 20 ). To maximize the template effect, tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (TFPB) was used as a weakly coordinating counterion for the sodium cation.…”
Section: Synthesis Of Hopf Link (Singly Interlocked) [2]catenanesmentioning
confidence: 99%
“…Nevertheless, an example of an alkaline cation template synthesis of a [2]catenane formed under thermodynamic control has been reported by Chiu and co-workers (Scheme 20 ). [ 86 ] The system combines diamine 69 with dialdehyde 70 through reversible imine bond formation in the presence of a sodium salt in a low polarity solvent to give the [2]catenane 72-Na I (Scheme 20 ). To maximize the template effect, tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (TFPB) was used as a weakly coordinating counterion for the sodium cation.…”
Section: Synthesis Of Hopf Link (Singly Interlocked) [2]catenanesmentioning
confidence: 99%
“…[12][13][14][15] Since the early report by Wasserman 16 of the synthesis of a [2]catenane wherein two rings-one a cycloalkane and the other a cyclic acyloin-are mechanically interlocked, numerous synthetic approaches [1][2][3][4] for constructing MIMs with exotic molecular structures have been described in the literature. These synthetic approaches, including the seminal contribution of Sauvage 17 in his Cu(I)-directed syntheses of catenates, depend on templation using either (1) strong noncovalent bonding forces, such as metal coordination [17][18][19][20][21][22][23] and donor-acceptor interactions [24][25][26] or (2) weak noncovalent bonding forces associated with hydrogen bonding [27][28][29][30][31] and hydrophobic effects. 32,33 Despite the large number of synthetic approaches available for preparing MIMs, the synthesis reported by Wasserman 16 remains one of the very few examples in the literature where a catenane is composed of a saturated cycloalkane ring.…”
Section: Introductionmentioning
confidence: 99%
“…2 By aligning two (or more) pyridine-type ligands into a polyhedral configuration, transition metal ions can also be useful templates for the construction of aesthetically appealing interlocked molecules and molecular knots 3 (e.g., trefoil knots, 4 Borromean rings, 5 Stars of David 6 ). 9 To explore the possible applications of [2]catenanes synthesized using this approach, we wished to investigate its synthetic flexibility by replacing one (or both) of the Na + ionaligned di(ethylene glycol) units with a longer analogue, providing hetero- [2]catenanes (two nonequivalent macrocyclic components) or larger homo- [2]catenanes. 8 Recently, we found that the Na + ion can template the orthogonal alignment of two di(ethylene glycol) chains, allowing the direct construction of a [2]catenane through the assembly of five components [two di(ethylene glycol)-containing diamines, two isophthalaldehydes, one Na + ion].…”
Section: Introductionmentioning
confidence: 99%